Problematising vocational education and training in schools: using student narratives to interrupt neoliberal ideology. Issue 4 (2nd October 2019) - Down, Barry; Smyth, John; Robinson, Janean
ABSTRACT: In Australia, like many western countries, there has been a convergence of education policy around a set of utilitarian and economistic approaches to vocational education and training in schools. Such approaches are based on the assumption that there is a direct relationship between national economic growth, productivity and human capital development resulting in the persuasive political argument that schools should be more closely aligned to the needs of the economy to better prepare 'job ready' workers. These common sense views resonate strongly in school communities where the problem of youth unemployment is most acute and students are deemed to be 'at risk', 'disadvantaged' or 'disengaged'. This article starts from a different place by rejecting the fatalism and determinism of neoliberal ideology based on the assumption that students must simply 'adapt' to a precarious labour market. Whilst schools have a responsibility to prepare students for the world of work there is also a moral and political obligation to educate them extraordinarily well as democratic citizens. In conclusion, we draw on the experiences of young people themselves to identify a range of pedagogical conditions that need to be created and more widely sustained to support their career aspirations and life chances.